Visual exploration patterns of human figures in action: an eye tracker study with art paintings - Villani, Daniela; Morganti, Francesca; Cipresso, Pietro; Ruggi, Simona; Riva, Giuseppe; Gilli, Gabriella (Frontiers in Psychology, 2015)
Art exploration is a complex process conditioned by factors at different levels and includes both basic visual principles and complex cognitive factors. The human figure is considered a critical factor attracting the attention in art painting. Using an eye-tracking methodology, the goal of this study was to explore different elements of the human figure performing an action (face and body parts in action) in complex social scenes characterized by different levels of social interaction between agents depicted in scenes (individual vs. social). The sample included 44 laypersons, and the stimuli consisted of 10 fine art paintings representing the figurative style of classical art. The results revealed different scanning patterns of the human figure elements related to the level of social interaction of agents depicted in the scene. The agents’ face attracted eye movements in social interaction scenes while the agents’ body parts attracted eye movements only when the agents were involved in individual actions. These processes were confirmed specifically in participants with high empathic abilities who became immediately fixated on faces to develop a mimetic engagement with other agents. Future studies integrating other measures would help confirm the results obtained and strengthen their implication for embodiment processes.